The Effectivity Of Aplication Mycorrhiza Toward Absorpstion Of Nitrogen (N) and Phosporus (P) In the Land with Drought Stress That Have Been Given Organic Matter In The Village Aek Godang Districts Hulu Sihapas Regercy North Padang Lawas. - Asmarlaili Sahar; Hardy Guchi (Universitas Sumatera Utara, 2018)
Rubber is one of the biggest commodity plantation featured in Indonesia. The development of the rubber is centered on the area with precipitation 2500-4000 mm/year. On the area of the rubber exposed to the many problem of competition for land and many attacks of the disease so that need to maximize the potential of the area which low rainfall. But also the area has its own problem especially absorption hara. One effort that can be to resolve the issue is the giving of mycorrhiza and organic materials to increase absorbtion hara on such plants.This research had been conducted populate plantation in the village of Aek Godang, district of Hulu Siapas, regency of Padang Lawas Utara, North Sumatera. In the month March until Juli 2016. Aimed to the test the influence of mycorrhiza toward absorption of Nitrogen (N) and Phosporus (P) the seeds application of the rubber clone PB 260 on the land with the strees of the drought that has been given organic material. Method of this research was non factorial random sampling block design with three treatments, that was M0: Without Mycorrhiza, M1: Accaulospora 100g/Plant, M2 : Glomus+Acaulospora (1:1) 100g/Plant with every treatment there was 10 replicant of the experiment showed that application mycorrhiza enhanced the increase absorption N and P compared to the not aplication mycorrhiza. Keywords : Mycorrhiza, Organic Matter, Rubber